2015
DOI: 10.1097/nmd.0000000000000330
|View full text |Cite
|
Sign up to set email alerts
|

Relationships of Childhood Adverse Experiences With Mental Health and Quality of Life at Treatment Start for Adult Refugees Traumatized by Pre-Flight Experiences of War and Human Rights Violations

Abstract: Adverse and potentially traumatic experiences (PTEs) in childhood were examined among 54 adult refugee patients with pre-flight PTEs of war and human rights violations (HRVs) and related to mental health and quality of life at treatment start. Extent of childhood PTEs was more strongly related to mental health and quality of life than the extent of war and HRV experiences. Childhood PTEs were significantly related to arousal and avoidance symptoms of posttraumatic stress disorder (PTSD) and to quality of life,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
68
1
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 64 publications
(70 citation statements)
references
References 72 publications
(92 reference statements)
0
68
1
1
Order By: Relevance
“…Prevalence rates of psychological distress in our unselected group of undocumented migrants in Norway were extremely high and considerably higher than results from studies on mental health among refugees in Norway (Jakobsen et al 2011, Teodorescu et al 2012a) and in undocumented migrants (Coffey et al 2010), consistent with, or higher than, those in other refugee populations and populations living in postwar areas (Lopes Cardozo et al 2004, 2005, Steel et al 2011) and approximately as high as levels found in traumatised psychiatric outpatients with a refugee background in Norway (Opaas & Varvin 2015).…”
Section: Discussioncontrasting
confidence: 45%
See 1 more Smart Citation
“…Prevalence rates of psychological distress in our unselected group of undocumented migrants in Norway were extremely high and considerably higher than results from studies on mental health among refugees in Norway (Jakobsen et al 2011, Teodorescu et al 2012a) and in undocumented migrants (Coffey et al 2010), consistent with, or higher than, those in other refugee populations and populations living in postwar areas (Lopes Cardozo et al 2004, 2005, Steel et al 2011) and approximately as high as levels found in traumatised psychiatric outpatients with a refugee background in Norway (Opaas & Varvin 2015).…”
Section: Discussioncontrasting
confidence: 45%
“…, , Steel et al . ) and approximately as high as levels found in traumatised psychiatric outpatients with a refugee background in Norway (Opaas & Varvin ).…”
Section: Discussionmentioning
confidence: 75%
“…In interviews with migrants, being an outsider to the community can have both advantages and disadvantages. It can reduce fear of gossip and judgement if the informant reveals experiences and considerations that clash with sociocultural norms within the community (Opaas and Varvin 2015). However, the lack of a shared language and experiences may reduce mutual understanding of subtleties.…”
Section: Methodsmentioning
confidence: 99%
“…It has repeatedly been shown that refugees as a group has endured many potentially traumatizing experiences before and during flight such as near‐death experiences, seeing close ones be maltreated or killed, torture, rape and so forth. Most researches find higher levels of known post‐traumatic conditions in refugee populations like post‐traumatic stress disorder (PTSD), anxiety disorders, depressions, somatizing disorders and psychotic disorders (see for example Alemi, James, Cruz, Zepeda, & Racadio, ; Drozdek, Kamperman, Tol, Knipscheer, & Kleber, ; Kroll, Yusuf, & Fujiwara, ; Opaas & Varvin, ; Teodorescu, Heir, Hauff, Wentzel‐Larsen, & Lien, ; Vaage et al, ; Vervliet, Lammertyn, Broekaert, & Derluyn, ). The complex traumatizing experiences of refugees may disturb personality functions, relational functions, affect regulation and somatic regulation (Allen & Fonagy, ; Allen, Vaage, & Hauff, ; Rosenbaum & Varvin, ; Schore, ; Varvin & Rosenbaum, ).…”
Section: Current Situation Of Refugeesmentioning
confidence: 99%